Modernismo, socialismo e exílio: Alexander Altberg no Rio de Janeiro da Era Vargas (1930-1945) - Liszt Vianna Neto (2014)
The exile of European architects in the Americas is one of the main events in the history of modern twentieth century architecture. This research concerns the trajectory of Alexander Altberg as a case study in this exile process. He was a Berliner architect who immigrated to Rio de Janeiro in 1931, and was also a former student of the Bauhaus and apprentice of the prominent architect Arthur Korn. Altberg acted not only as an architect and main producer of the avant-gardist Base magazine, but also as an important representative of German modernism in the Brazilian modernist network. In Brazil, he had contact with modernist groups from Sao Paulo, such as CAM and SPAM, with the AAB and Pró-Arte in Rio, and with the main figures of the Brazilian modernist context: L. Segall, G. Warchavchik, M. de Andrade, L. Costa, among others. As many German immigrants in the 30s, the exercise of his professor was vetted by the Vargas government and his memory eclipsed by the dominance of the Carioca School. The memory of Altberg, as well as the first modern architects in Brazil, is the main subject of this research and critique of architecture.